Periodontal health in an indigenous Sámi population in Northern Norway: a cross-sectional study - Ann-Kristine Sara Bongo; Magritt Brustad; Nils Oscarson; Birgitta Jönsson (BMC, 2020)
Abstract Background The aim of the study was to describe prevalence, severity and distribution of periodontal disease as well as associated risk factors in an indigenous Sámi population in Northern Norway, and to investigate differences between the indigenous Sámi and the non-Sámi population. Methods This cross-sectional study included data from the Dental Health in the North study (N = 2078; 18-75 years). Data on Ethnicity, household income, education, smoking habits, dental attendance, and tooth brushing habits were collected by a questionnaire. Periodontal conditions were assessed by clinical examination. A modified version of the new AAP/EFP classification system of periodontal disease was used to estimate the severity of periodontitis. Three stages were used: 'Non-severe periodontitis', 'Stage II', and stage 'III/IV'. Results Of the total study population 66.5% reported Sámi affiliation. The total prevalence of periodontitis was 49.7%, with 20.1% in Stage III/IV, but no differences between Sámi and non-Sámi. When controlled for sex, age, education, smoking and dental attendance the Sámi had higher probability of having more severe stages of periodontitis; Odds RatioStage II (OR) = 1.3; 95% CI: 1.1-1.7; and ORStage III/IV (OR) = 1.6; 95% CI: 1.1-2.2) compared to non-Sámi. The Sámi had higher prevalence of periodontal pocket depth (PD) ≥ 4 mm (t = 1.77; p <  0.001) and PD ≥ 6 mm (t = 1.08; p = 0.038) than the non-Sámi. Conclusions The prevalence of periodontitis was high in communities in the core area of Sámi settlement in Northern Norway, regardless of ethnicity. People with Sámi ethnicity had more deep periodontal pockets and an increased odds of having severe stages of periodontitis. Future studies should address possible explaining factors behind the potential higher risk of having more severe periodontitis among indigenous people in Sámi settlements.